PENGEMBANGAN APLIKASI BERBASIS ANDROID BeMAU UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA ANAK USIA DINI - Noor Rokhmah Affifah; Umi Faizah (STPI Bina Insan Mulia Yogyakarta, 2023)
The background of this research is the lack of learning media to improve AUD reading skills in the digital era. The formulation of the research problems are: 1) what is the design for the development of the